2015
DOI: 10.3748/wjg.v21.i31.9337
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30b suppresses tumor migration and invasion by targeting EIF5A2 in gastric cancer

Abstract: Our findings describe a link between miR-30b and EIF5A2, which plays an important role in mediating epithelial-mesenchymal transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Among the results in this research, one of them implied that miR‐30b and miR‐30d were poorly expressed, and CEACAM1 was highly expressed in liver tissues of FHF mice and serum of FHF patients. Similarly, down‐regulation of miR‐30b in gastric cancer cell lines and tissues has been unraveled in a recent literature . Xiong et al have pointed out that members of the miR‐30 family, particularly miR‐30b was depleted in triple‐positive pancreatic cancer stem cells .…”
Section: Discussionmentioning
confidence: 88%
“…Among the results in this research, one of them implied that miR‐30b and miR‐30d were poorly expressed, and CEACAM1 was highly expressed in liver tissues of FHF mice and serum of FHF patients. Similarly, down‐regulation of miR‐30b in gastric cancer cell lines and tissues has been unraveled in a recent literature . Xiong et al have pointed out that members of the miR‐30 family, particularly miR‐30b was depleted in triple‐positive pancreatic cancer stem cells .…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have demonstrated that EIF5A2 exhibits its tumorigenic effects via activation of the phosphoinositide-3-kinase/Rac-α serine/threonine-protein kinase signaling pathway (15,25) and its induction of matrix metalloproteinase 2 protein expression (26). In addition, EIF5A2 reduces expression of E-cadherin and increases expression of Vimentin (26,27), and may activate transforming protein RhoA precursor/Rac1 signaling pathways (24). Additionally, a previous study identified zinc finger protein Gli1 as a putative transcription factor for EIF5A2 (28).…”
Section: Discussionmentioning
confidence: 99%
“…miR-30b has been previously described as a tumor suppressor in certain types of cancer, including NSCLC, gastric cancer and colorectal cancer (CRC) (14,21,22). Conversely, miR-30b has been described as an oncogene in bladder cancer (23), oral squamous cell cancer (10) and medulloblastoma (24).…”
Section: Discussionmentioning
confidence: 99%
“…In certain types of cancer, the mechanism of miR-30b is understood. Tian et al (22) demonstrated that miR-30b regulated gastric cancer cell processes by targeting eukaryotic translation initiation factor 5A2. In gastric cancer, Zhu et al (15) indicated that miR-30b could promote cell apoptosis and suppress tumor growth in vivo by targeting plasminogen activator inhibitor-1.…”
Section: Discussionmentioning
confidence: 99%